Developing narrative identities in youth pre-elite sport: bridging the present and the future - Ronkainen, N. J.; Ryba, T. V. (Qualitative Research in Sport, Exercise and Health, 2020)
Narrative research has contributed to understandings of athletic identity as an evolving story of the self that is creatively put together by the agentic individual but necessarily dependent on broader narratives within which we all live our lives. However, most studies in sport have focused on retrospective `big stories` of athletes` lives, rather than on-going, future-oriented identity construction through storytelling. In this study, we explored Finnish pre-elite athletes` emerging stories of the self to understand the processes associated with the narrative selection and the resources they tap into in making sport meaningful to them. Nine women and eight men aged 17-18 were invited to create a visual representation of themselves as athletes and discuss them in conversational interviews. In the narrative analysis, we identified three storylines, `the high-performance athlete`, `the performance, relational and fun athlete` and `the lifestyle athlete` and explored how stories were selected to construct a positive athletic identity and sustain motivation. We argue that the end point of the identity narratives was to establish a positive future perspective and hope in the face of adversities. The future-oriented narrative content signals a need for more diverse narrative methodologies in sport beyond retrospective approaches such as the life story interview, especially with younger participants.